2022
DOI: 10.1186/s13561-022-00385-9
|View full text |Cite
|
Sign up to set email alerts
|

An (un)healthy social dilemma: a normative messaging field experiment with flu vaccinations

Abstract: Background Influenza seasons can be unpredictable and have the potential to rapidly affect populations, especially in crowded areas. Prior research suggests that normative messaging can be used to increase voluntary provision of public goods, such as the influenza vaccine. We extend the literature by examining the influence of normative messaging on the decision to get vaccinated against influenza. Methods We conduct a field experiment in conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…However, one can be motivated to receive the flu shot for those two motivations simultaneously (at equal levels or one predominating the other). Mussio and de Oliveira (2022) showed that emphasizing at the same time self-interest and herd immunity aspects on a poster is the message that increases the most vaccination rate, compared to only one argument. A future study could test if combining self-interest and herd-immunity arguments prevents the decrease in the very high norm level observed when only the herd immunity motive is used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one can be motivated to receive the flu shot for those two motivations simultaneously (at equal levels or one predominating the other). Mussio and de Oliveira (2022) showed that emphasizing at the same time self-interest and herd immunity aspects on a poster is the message that increases the most vaccination rate, compared to only one argument. A future study could test if combining self-interest and herd-immunity arguments prevents the decrease in the very high norm level observed when only the herd immunity motive is used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the groups at risk for the disease (older adults and infants) do not exactly overlap with the group responsible for spreading the virus (young adults and children; Brewer et al, 2017; Chapman et al, 2012; Galvani et al, 2007; Halloran & Longini, 2006). This lag makes the vaccination decision resemble a social dilemma (individual costs and collective interests at stake; Betsch et al, 2013; Mussio & de Oliveira, 2022).…”
Section: A Norm-as-information Approachmentioning
confidence: 99%